The Tate Gallery : an illustrated companion to the National Collections of British & Modern Foreign Art. - Reid, Norman (London : Tate Gallery, 1979)
Picasso, Pablo ; Braque, Georges ; Gris, Juan ; Leger, Fernand ; Delaunay, Robert ; Duchamp-Villon, Raymond ; Balla, Giacomo ; Boccioni, Umberto ; Lewis, Wyndham ; Roberts, William ; Epstein, Jacob ; Bomberg, David ; Kandinsky, Wassily ; van der Leck, Bart ; Mondriaan, Piet ; Malevich, Kasimir ; Moholy-Nagy, Laszlo ; Gabo, Naum ; Bell, Vanessa ; González, Julio ; Brancusi, Constantin ; Hélion, Jean ; Chagall, Marc ; De Chirico, Giorgio ; Duchamp, Marcel ; Klee, Paul ; Ernst, Max ; Magritte, René ; Delvaux, Paul ; Dali, Salvador ; Miro, Joan ; Arp, Hans (Jean) ; Nash, John ; Hitchens, Ivon ; Wallis, Alfred ; Wadsworth, Edward ; Nicholson, Ben ; Richards, Ceri ; Burra, Edward ; Moore, Henry ; de Staël, Nicolas ; Matisse, Henri ; Dubuffet, Jean ; Jorn, Asger ; Tàpies, Antoni ; Guttuso, Renato ; Morandi, Giorgio ; Marini, Marino ; Giacometti, Alberto ; César ; Paolozzi, Eduardo ; Parc, Julio Le ; Bury, Pol ; Albers, Josef ; Vasarely, Victor ; Riley, Bridget ; Gorky, Arshile ; Pollock, Jackson ; Rothko, Mark ; Still, Clyfford ; Newman, Barnett ; Louis, Morris ; Noland, Kenneth ; Smith, David ; Bacon, Francis ; Freud, Lucian ; Smith, Jack ; Hepworth, Barbara ; Pasmore, Victor ; Martin, Kenneth ; Lanyon, Peter ; Scott, William ; Davie, Alan ; Hilton, Roger ; Hamilton, Richard ; Blake, Peter ; Kitaj, R.B. ; Lichtenstein, Roy ; Johns, Jasper ; Oldenburg, Claes ; Denny, Robyn ; Smith, Richard ; Cohen, Bernard ; Paolozzi, Eduardo ; King, Phillip ; Caro, Anthony ; Flanagan, Barry ; Caulfield, Patrick ; Hockney, David ; Phillips, Tom ; Boyle, Mark ; Andre, Carl ; LeWitt, Sol ; Stella, Frank ; Riverhead (New York) ; Long, Richard ; Becher, Bernd & Hilla ; Broodthaers, Marcel ; Tilson, Joe ; Warhol, Andy ; Lissitzky, El ; Kitaj, R.B.
Engels
This book was published on the occasion of the opening on 24 May 1979 of the largest extension ever made to the building of the Tate Gallery.
boek